2010
DOI: 10.7763/ijcee.2010.v2.133
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of Change Management in Dynamic Business Process

Abstract: Many business processes are highly dynamic and require changes even during execution. Existing commercial Business Process Management Systems (BPMS) fail to support such processes appropriately since they work in a rather static manner; they demand that the structure of a process is fixed before execution. The aim of this research is to provide a change management technique to improve the flexibility, adaptability, and dynamic of the current Business Process Modeling (BPM) approaches, and to help software engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Formal approach graph grammars for checking the consistency of UML class and sequence diagrams are proposed in [79]. In Rajabi and Lee [80]- [82], a change management framework to support runtime changes in business process modelling languages is proposed (where the business processes are modelled using UML diagrams). The new changes are the result of creating, deleting, or modifying business processes.…”
Section: Formal Semantics Approachesmentioning
confidence: 99%
“…Formal approach graph grammars for checking the consistency of UML class and sequence diagrams are proposed in [79]. In Rajabi and Lee [80]- [82], a change management framework to support runtime changes in business process modelling languages is proposed (where the business processes are modelled using UML diagrams). The new changes are the result of creating, deleting, or modifying business processes.…”
Section: Formal Semantics Approachesmentioning
confidence: 99%
“…Rajabi et al [7] propose that the processes must have flexible and adaptive execution which can evolve according to specific situations.…”
Section: Dynamic Business Processmentioning
confidence: 99%
“…The analysis showed that dynamic business processes are not understood and defined similar so other authors proposed dynamic model implementation solutions which we divided into two examined problems: changing business processes at runtime [1], [2], [4], [5], [10], [11] or executing business process with no predefined sequence of activities [7], [12]. In this section we provide realization for a different solution, which proposed by different authors.…”
Section: Model Implementation Solutionsmentioning
confidence: 99%
“…), or deterioration of global quality of the business process [7]. In this respect, the change management is an important subject in the life cycle of any business process and it has been actively persuaded, by the research community, for the last decade [8,9]. The main objective of this research is to identify the potential effects of a change and to estimate the needs to accomplish a change.…”
Section: Introductionmentioning
confidence: 99%